2012
DOI: 10.1093/jxb/ers321
|View full text |Cite
|
Sign up to set email alerts
|

Phenological response of grassland species to manipulative snowmelt and drought along an altitudinal gradient

Abstract: Plant communities in the European Alps are assumed to be highly affected by climate change, as the temperature rise in this region is above the global average. It is predicted that higher temperatures will lead to advanced snowmelt dates and that the number of extreme weather events will increase. The aims of this study were to determine the impacts of extreme climatic events on flower phenology and to assess whether those impacts differed between lower and higher altitudes. In 2010, an experiment simulating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 66 publications
2
35
1
Order By: Relevance
“…C. defloratus shifted its phenology by 3.28 day 100/m, P. orbiculare by 3.26 day 100/m, and T. pratense by 3.06 day 100/m, the other species were less responsive. Other observational studies in alpine grasslands showed an average delay of 3.8 day 100/m (Cornelius, Estrella, et al., 2013; Cornelius, Leingärtner, et al., 2013). Interestingly, for A. foetida and M. perennis, the reaction was much less pronounced compared to the observations on these species reported by Cornelius, Estrella, et al., 2013 and Cornelius, Leingärtner, et al., 2013; 2.19 day 100/m instead of 3.7 day 100/m for A. foetida and 0.85 day 100/m compared to 3.5 day 100/m for M. perennis , respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. defloratus shifted its phenology by 3.28 day 100/m, P. orbiculare by 3.26 day 100/m, and T. pratense by 3.06 day 100/m, the other species were less responsive. Other observational studies in alpine grasslands showed an average delay of 3.8 day 100/m (Cornelius, Estrella, et al., 2013; Cornelius, Leingärtner, et al., 2013). Interestingly, for A. foetida and M. perennis, the reaction was much less pronounced compared to the observations on these species reported by Cornelius, Estrella, et al., 2013 and Cornelius, Leingärtner, et al., 2013; 2.19 day 100/m instead of 3.7 day 100/m for A. foetida and 0.85 day 100/m compared to 3.5 day 100/m for M. perennis , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, studies report the onset of a phenological stage as day of the year, that is, first flowering day, FFD (e.g., Cornelius, Estrella, Franz, & Menzel, 2013; Cornelius, Leingärtner, et al., 2013; Fitter & Fitter, 2002). A complementary approach would be to measure the temperature accumulation reached to start flowering, or more specifically, the growing degree days to start FFD (GDD FFD ; de Réaumur, 1735).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, experimental studies indicate that subalpine meadows are sensitive to climate change manipulations, reporting either community or species-specific responses (Cornelius et al 2013; Dunne et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…Field work for data collection and/or analysis usually represents a big effort for researchers, so a key question would be which experimental protocol (number and distribution of observation units) is required to track IAV of a given phenological variable and, among different observational approaches, which are more suitable to investigate IAV in the context of a long-term monitoring programme. Reducing sampling effort is laudable especially in the monitoring of remote areas (Cornelius et al 2011). Previous sample size analyses suggest that a sample size of 15 sampling units and a fortnightly frequency is the minimum requirement for tracking a seasonal phenological trajectory in deciduous forest ecosystems (Morellato et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term records indicate that earlier phenological development [3,4], range shifts [5,6] and shrinking habitats [7] are all in progress now.…”
Section: Introductionmentioning
confidence: 99%